Sistem Pendukung Keputusan Pemilihan Tenaga Hononer Terbaik Menggunakan Metode Additive Ratio Assessment (ARAS) Dengan Pembobotan Rank Order Centroid (ROC) - Simangunsong, Evi O; Hasibuan, Nelly Astuti; Siregar, Annisa Fadillah (CV. Graha Mitra Edukasi, 2023)
Honorary workers are employees who have not been appointed as permanent employees who receive an honorarium every month from the agency or company where they work. SMK N 1 Balige is one of the schools that still needs honorary teachers. Each school certainly makes policies to create a teaching and learning process between teachers and students that is more conducive and optimal. One of the policies of SMK N 1 Balige is to select the best honorary teachers. This policy can encourage honorary teachers to work more professionally. However, this assessment is still carried out manually so that it affects the results of decisions that are not objective. Then a decision support system is needed by applying two methods, namely the Additive Ratio Assessment (ARAS) and Rank Order Centroid (ROC) methods to produce accurate decisions and get the best alternative from the input matrix. The ARAS method is used as the ranking for the final results and the ROC method is used for weighting. The application of a decision support system using the ROC method is able to give weight to each criterion that will be used in the ARAS method calculation process. By applying the ARAS method, the best alternative was produced in the name of Donna Napitupulu with alternative code A3 with a result of 0.976 followed by alternative A1 in the name of Anita Teresia Sianipar with a result of 0.929.